Kepercayaan, Cinta dan Pengalaman : Jalur Menuju Kepuasan Pelanggan dalam Sistem Pembayaran Elektronik - Oktoviandi, Ivan; Bastaman, Aam (BUDGETING : Journal of Business, Management and Accounting, 2024)
This study aims to analyze the effect of brand trust and brand love on customer satisfaction mediated by customer experience on PT Artajasa Pembayaran Elektronis partners who use ATM Bersama Debit and/ or ATM Bersama QR and/ or Managed Service EDC services and the sample criteria are Business PIC or Technical PIC or Operational PIC. This research uses Partial Least Square (PLS) with the help of the SmartPLS program (v.4.0). Structural Equation Modeling (SEM) is divided into two, namely inner model and outer models as well as descriptive analysis tests and mediation tests. In this study, the data analysis that will be carried out by the outer model is validity test, reliability test, R-Square and SRMR test while the data analysis that will be carried out on the inner model is multicollinearity test, Path Coefficient Test, P-Value Test and F-Square Test. For descriptive analysis test using skewness value and kurtosis value and for mediation test using Upsilon V. The results showed that there is no significant influence between brand trust with customer satisfaction and brand love with customer satisfaction and brand love has no influence on customer satisfaction through customer experience. And also shows that there is a significant influence between brand trust with customer experience, there is a significant influence between brand love with customer experience and brand trust has an influence on customer satisfaction through customer experience. Keywords: Brand Trust, Brand Love, Customer Experience, Customer Satisfaction